Microstructure and Properties of Selected Magnesium-Aluminum Alloys Prepared for SPD Processing Technology - Cizek L. (Archives of Metallurgy and Materials, 2017)
A growing interest in wrought magnesium alloys has been noticed recently, mainly due to development of various SPD (severe plastic deformation) methods that enable significant refinement of the microstructure and – as a result – improvement of various functional properties of products. However, forming as-cast magnesium alloys with the increased aluminum content at room temperature is almost impossible. Therefore, application of heat treatment before forming or forming at elevated temperature is recommended for these alloys. The paper presents the influence of selected heat treatment conditions on the microstructure and the mechanical properties of the as-cast AZ91 alloy. Deformation behaviour of the as-cast AZ61 alloy at elevated temperatures was analysed as well. The microstructure analysis was performed by means of both light microscopy and SEM. The latter one was used also for fracture analysis. Moreover, the effect of chemical composition modification by lithium addition on the microstructure of the AZ31-based alloy is presented. The test results can be helpful in preparation of the magnesium-aluminum alloys for further processing by means of SPD methods.